Effect of BMI on the value of serum progesterone to predict clinical pregnancy outcome in IVF/ICSI cycles: a retrospective cohort study - Shen, Zhaoyang; Luo, Xiaoyan; Xu, Jianming; Jiang, Yuqing; Chen, Wenhui; Yang, Qingling; Sun, Yingpu (Frontiers in Endocrinology, 2023)
Abstract Background: Numerous research has investigated the predictor role of progesterone (P) level on the human Chorionic Gonadotropin (hCG) trigger day of assisted reproductive technology (ART) outcomes. However, the relationship of progesterone levels on hCG day to clinical pregnancy outcomes in IVF/ICSI cycles for patients with different BMI groups is still elusive. This study aimed to investigate the effects of progesterone elevation on triggering day on clinical pregnancy rate (CPR) of IVF/ICSI cycles in patients with different female BMI. Methods: We conducted a retrospective cohort study that included 6982 normal-weight parents (18.5Kg/m2≤BMI<25Kg/m2) and 2628 overweight/obese patients (BMI≥25Kg/m2) who underwent fresh day 3 cleavage embryo transfer (ET) in IVF/ICSI cycles utilizing GnRH agonist to control ovarian stimulation. Results: The interaction between BMI and P level on triggering day on CPRs was significant (P<0.001). The average level of serum P was downregulated with the increase in maternal BMI. Serum P adversely affected CPR in distinct BMI groups. In the normal weight group, CPRs were downregulated as serum P concentrations gradually increased (P<0.001 for overall trend). The CPRs (lower than 65.8%) of progesterone level > 1.00 ng/ml on triggering day were significantly lower than that (72.4%) of progesterone level <0.5 ng/ml. In the overweight/obese group, CPRs showed a decrease statistically with progesterone levels of ≥2.00 ng/ml compared to progesterone levels of <0.5 ng/ml (51.0% VS. 64.9%, P<0.05). After adjusting for confounders, PE negatively correlated with CPRs only in the normal weight group (OR: 0.755 [0.677–0.841], P<0.001), not in the overweight/obese group (P =0.063). Conclusion: Women with higher BMI exhibited a lower progesterone level on triggering day. Additionally, PE on hCG day is related to decreased CPRs in GnRH agonist IVF/ICSI cycles with cleavage embryo transfers regardless of women's BMI level (normal weight VS. overweight/obesity).